Core strength training of amateur teen male swimming athlete - Xin, W. (Frontiers in Sport Research, 2020)
At present, in China, the strength training for young swimmers (especially the high-level athletes who are in the stage of achieving performance standards) mostly uses traditional strength training methods, and how to systematically carry out core strength training to improve the muscle strength of swimmers balance and special technology lacks theoretical and practical application. As the application of core strength training in competitive swimming at home and abroad is getting deeper and more detailed, how to specifically combine core strength training with water training to establish a more scientific and reasonable training system is the current need for young swimmers.